Traqueobroncopatia osteocondroplástica em portador de tumor de klatskin: Relato de caso e revisão da literatura - Faig-Leite, Fabíola Sawaguchi [UNESP] (2008)
Tracheopathia osteochondroplastica (TO) is an unusual idiopathic disorder, characterized by osteocartilaginous nodules in the submucosa of the respiratory airway, which causes rigidity and narrowing of the respiratory tree. It affects mainly men over 50 and clinical manifestations are due to obstruction and/or local infections. The pathogenesis is uncertain. We report a case of TO found incidentally in an autopsy of a 73 year-old woman, who had an extrahepatic biliary ductal carcinoma (Klatskin tumor).